2002
DOI: 10.3109/j180v01n01_09
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of a Rehabilitation Exercise Program on Head Repositioning Accuracy and Reported Levels of Pain in Chronic Neck Pain Subjects

Abstract: Objectives. Currently, there is limited research on the effectiveness of rehabilitative exercises for neck pain patients generally, and chronic neck pain patients in particular. Interestingly, recent evidence suggests that dysfunction of cervicocephalic kinesthesia, as measured by head repositioning accuracy (HRA), is present in many chronic patients, and that active eye-head-neck, co-ordination exercises, may be useful in terms of patients' rehabilitation.The purpose of this study was twofold: i. to determine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
41
1
3

Year Published

2004
2004
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(50 citation statements)
references
References 18 publications
(25 reference statements)
5
41
1
3
Order By: Relevance
“…The results are also consistent with the only available study comparing exercise (4-week) and WL in chronic neck pain [18]. The results from the present study demonstrate more between group changes than those reported in individuals with WAD by Vikne et al [14] and Michaleff et al [15].…”
Section: Previous Researchsupporting
confidence: 92%
See 2 more Smart Citations
“…The results are also consistent with the only available study comparing exercise (4-week) and WL in chronic neck pain [18]. The results from the present study demonstrate more between group changes than those reported in individuals with WAD by Vikne et al [14] and Michaleff et al [15].…”
Section: Previous Researchsupporting
confidence: 92%
“…As WAD patients may show changes in condition over time without intervention, comparison of some exercise interventions to no treatment might be useful in guiding rehabilitation protocols. Except for a small study by Humphreys & Ingens [18], no study has investigated individuals with chronic WAD who either performed exercise or remained at waiting list without any intervention. Humphreys & Ingens [18] investigated the effect of proprioceptive training with eye-head-neck exercises in a sample of 28 patients with chronic (>3 months) neck pain, where 61% had previously had a whiplash injury.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is some evidence that programs that emphasize gaze stability, eye head co-ordination and cervical position sense and balance tasks without local cervical spine treatment have resulted in either decreased medication intake, improved neck pain and disability, HRA and or balance in those with neck pain (Revel et al , 1994, Fitz-Ritson, 1995, Humphreys and Irgens, 2002, Jull et al, 2007, Treleaven, 2010. Improvements in balance and symptoms of dizziness have also been observed following a vestibular or oculomotor rehabilitation program or tailored sensorimotor program in patients with persistent WAD (Hansson et al , 2006, Storaci et al , 2006, Treleaven, 2010.…”
Section: Discussionmentioning
confidence: 99%
“…52,102,116 Vestibular rehabilitation programs have been shown to be useful in those with concussion 1,45 and resulted in improved balance and dizziness in individuals with WAD. 27 Interestingly, in those with WAD, this training did not improve neck pain or movement.…”
Section: Addressing Adaptive Changes In the Sensorimotor Control Systemmentioning
confidence: 99%